[8+3]-cycloaddition of tropones with azaoxyallyl cations - Roy, Tony; Jacob, Anu; Bhattacharjee, Subrata; Biju, Akkattu T. (Chemistry-An Asian Journal, 2019)
Although azaoxyallyl cations are widely used as 1,3-dipoles for various cycloaddition reactions leading to nitrogen-containing heterocycles, their application in higher-order cycloaddition reaction remains scarce. Herein, we present the [8+3]-cycloaddition reaction of tropones with in situ generated azaoxyallyl cations allowing the one-step construction of cycloheptatriene-fused 1,4-oxazinones in moderate to good yields. This base-promoted new carbon-oxygen and carbon-nitrogen bond-forming reaction takes place under mild conditions in the absence of transition metal catalysts.
Keywords: 1; 4-oxazinones; azaoxyallyl cations; heterocycles; tropones; [8+3] cycloaddition

Aryne Sommelet-Hauser rearrangement - Roy, Tony; Gaykar, Rahul N.; Bhattacharjee, Subrata; Biju, Akkattu T. (Chemical Communications, 2019)
An aryne induced transition-metal-free and mild Sommelet-Hauser rearrangement of tertiary benzylamines for the synthesis of -aryl amino acid derivatives in moderate to good yields is presented. Unlike the conventional Sommelet-Hauser rearrangement of ammonium salts, the methodology developed herein requires neither harsh conditions nor strong bases. Moreover, a temperature dependent switchable selectivity for the Sommelet-Hauser and Stevens [1,2] rearrangements has been observed.

Rapid synthesis of zwitterionic phosphonium benzoates by a three-component coupling involving phosphines, arynes and CO2 - Bhattacharjee, Subrata; Raju, Anjali; Gaykar, Rahul N.; Gonnade, Rajesh G.; Roy, Tony; Biju, Akkattu T. (Chemistry-An Asian Journal, 2020)
A mild and easy to perform multicomponent coupling involving phosphines, arynes generated from 2-(trimethylsilyl)aryl triflates, and CO(2)allowing the transition-metal-free synthesis of zwitterionic phosphonium benzoates has been developed. The reaction proceeds via the generation of 1 : 1 zwitterionic intermediates from phosphines and arynes followed by the interception with CO(2)to deliver the carboxylates in moderate to good yields instead of the anticipated benzooxaphosphol-3(1H)-ones.
Keywords: arynes; Carbon dioxide; multicomponent coupling; Phosphines; zwitterions